Nerve-injury induced changes to GluR1 and GluR2/3 sub-unit expression in area 3b of adult squirrel monkeys: developmental recapitulation? - Mowery, Todd M.; Garraghty, Preston E. (Frontiers in Systems Neuroscience, 2009)
The primate somatosensory system provides an excellent model system with which to investigate adult neural plasticity. Here, we report immunohistochemical staining data for the GluR1 and GluR2/3 AMPA receptors subunits in somatosensory area 3b one week after median nerve crush in adult squirrel monkeys. We find transcortical increases in the staining intensity of GluR1 AMPAR subunits and transcortical decreases in GluR2/3 AMPAR subunits. This pattern of change in the staining intensity of these subunits differs from the changes one would expect if the deprived cortical neurons were undergoing homeostatic synaptic scaling, or from ones that would follow NMDA receptor-mediated long-term potentiation. Indeed, this pattern of change appears to recapitulate proportions that exist early in development as if the deprived cortex has reverted to an immature state. We suggest that this state represents yet another stage of peripheral nerve injury-induced reorganization in adult primate somatosensory cortex, and may well be essential for subsequent NMDA receptor-mediated plasticity.